Intestinal microbiota – a possible contributor to cardiovascular diseases? - Roua Iorga; Ovidiu Gabriel Bratu; Nicolae Bacalbasa; Mihnea-Alexandru Gaman; Camelia Cristina Diaconu (Journal of Mind and Medical Sciences)
The intestinal microbiota represents an interesting and emergent field of research, with already known implications in metabolic and immunological functions. Recently, there is increasing evidence that specific gut microbial populations are associated with cardiovascular diseases. Numerous completed and ongoing studies aim to evaluate the potential of intestinal microbiota assessment to improve the prevention, diagnosis, and therapeutic arsenal of cardiovascular diseases, considering dysbiosis as a cardiovascular risk factor. There is strong evidence for a correlation between intestinal flora imbalance and metabolic changes secondary to bacterial metabolites. In this minireview, we discuss recent data about the connections between intestinal microbiota and cardiovascular disease.